2010
DOI: 10.1159/000320283
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Cord Blood Homocysteine and Folic Acid Levels in Smoking and Nonsmoking Pregnant Women

Abstract: Introduction: The homocysteine level in blood is affected by gender, diet, smoking, folic acid and B-complex vitamins. It is known that higher than normal homocysteine levels in plasma may cause vascular endothelium dysfunction, resulting in the promotion of thrombus formation. In our study, we aimed to assess the effects of smoking during pregnancy on the homocysteine and folic acid levels of the mother and baby. Methods: The study included 58 pregnant women who had completed their 37th week of gestation: 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…One of these found a significant negative association (lower levels) of smoking with umbilical cord blood levels of folate (Stark et al, ). The other six studies did not report significant associations (Adaikalakoteswari et al, ; Ambroszkiewicz et al, ; Coker et al, ; Hay et al, ; Relton et al, ; Sram et al, ). One study described serum levels of folate during pregnancy measured at four different time points (0–10, 11–20, 21–30, and 31–40 weeks; van Wersch et al, ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…One of these found a significant negative association (lower levels) of smoking with umbilical cord blood levels of folate (Stark et al, ). The other six studies did not report significant associations (Adaikalakoteswari et al, ; Ambroszkiewicz et al, ; Coker et al, ; Hay et al, ; Relton et al, ; Sram et al, ). One study described serum levels of folate during pregnancy measured at four different time points (0–10, 11–20, 21–30, and 31–40 weeks; van Wersch et al, ).…”
Section: Resultsmentioning
confidence: 98%
“…Of the remaining 95 papers, 63 were excluded on the basis of the full text. The remaining 32 articles are included in this review, as shown in Supplemental S1 (Adaikalakoteswari et al, ; Ambroszkiewicz, Chelchowska, Lewandowski, Gajewska, & Laskowska‐Klita, ; Baker et al, ; Bakker et al, ; Bergen et al, ; Bodnar et al, ; Coker et al, ; Dayaldasani et al, ; Frery et al, ; D. Furness et al, ; D. L. Furness, Yasin, Dekker, Thompson, & Roberts, ; Gadowsky et al, ; Hay et al, ; Jauniaux, Johns, Gulbis, Spasic‐Boskovic, & Burton, ; Knight et al, ; Knudtson et al, ; Larroque et al, ; Matsuzaki et al, ; McDonald, Perkins, Jodouin, & Walker, ; Mito et al, ; Nilsen et al, ; Ozerol, Ozerol, Gokdeniz, Temel, & Akyol, ; Pagan, Hou, Goldenberg, Cliver, & Tamura, ; Prasodjo et al, ; Relton et al, ; Sram, Binkova, Lnenickova, Solansky, & Dejmek, ; Stark et al, ; Stark, Pawlosky, Sokol, Hannigan, & Salem Jr., ; Van Uitert et al, ; van Wersch, Janssens, & Zandvoort, ; Vandevijvere, Amsalkhir, Van Oyen, & Moreno‐Reyes, ; Yila et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study does not confirm fetal programming of the expression patterns of the mentioned enzymes. Other intrauterine factors may have an impact on fetal programming (e.g., smoking during pregnancy leading to an increase of homocysteine (35) and placental mitochondrial dysfunction (36)) (37). …”
Section: Resultsmentioning
confidence: 99%
“…30 Since prenatal smoking is strongly associated with elevated levels of homocysteine concentrations, one would expect the same relationship between homocysteine and fetal telomere length as observed among smoking mothers. 31 In a study of 77 pregnant women, homocysteine levels were measured from cord blood at delivery. Maternal homocysteine levels were not significantly related to the telomere length of cord leukocytes in the neonates.…”
mentioning
confidence: 99%